Recycling of the Rare Earth Oxides from Spent Rechargeable Batteries Using Waste Metallurgical Slags - Tang, Kai; Ciftja, Arjan; van der Eijk, Casper; Wilson, Shawn; Tranell, Gabriella (Journal of Mining and Metallurgy, Section B: Metallurgy, 2013)
A high temperature process for recycling spent nickel-metal hydride rechargeable batteries has been recently developed at SINTEF/NTNU. The spent battery modules were first frozen with liquid nitrogen for the de-activation and brittle fracture treatment. The broken steel scraps and plastics were then separated by the mechanical classification and magnetic separation. The remaining positive and negative electrodes, together with the polymer separator, were heated to 600-800oC in order to remove the organic components and further separate the Ni-based negative electrode. XRF analyses indicate that the heat-treated materials consist mainly of nickel, rare earth and cobalt oxides. The valuable rare earth oxides were further recovered by the high-temperature slagging treatment. The waste metallurgical slags, consist mainly of SiO2 and CaO, were used as the rare earth oxide absorbent. After the high temperature slagging treatment, over 98% of nickel and cobalt oxides were reduced to the metal phase; meanwhile almost all rare earth oxides remain in the molten slags. Furthermore, EPMA and XRF analyses of the slag samples indicate that the rare earth oxides selectively precipitate in the forms of solid xSiO2∙yCaO∙zRe2O3. The matrix of slag phase is Re2O3 deficient, typically being less than 5 wt%. This provides a sound basis to further develop the high-temperature process of concentrating the Re2O3 oxides in slags.